Step-by-step explanation:
We multiply it to find the product
positive times positive = positive
positive times negative = negative
negative times positive = negative
negative times negative = positive
[tex](-\frac{1}{3})(-\frac{1}{3})= \frac{1}{9}[/tex]
Negative and negative is positive , so product is positive
[tex](-\frac{1}{3})(\frac{1}{3})= -\frac{1}{9}[/tex]
Negative and positive is negative , so product is negative
[tex](\frac{1}{3})(-\frac{1}{3})= -\frac{1}{9}[/tex]
positive and negative is negative , so product is negative
[tex](\frac{1}{3})(\frac{1}{3})= \frac{1}{9}[/tex]
positive and positive is positive , so product is positive